2017
DOI: 10.1177/1055665617726999
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Alveolar Bone Grafting in Patients Born With Unilateral Cleft Lip and Palate

Abstract: Patients rehabilitated with complex dental restoration seems to be at higher risk for progression of bone loss in the cleft area. Supportive periodontal therapy should be implemented after complex dental restorations in cleft patients. Conventional occlusal radiographs provide an adequate image for evaluating postoperative bone height in clinical follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
1
11
0
2
Order By: Relevance
“…5,8,[17][18][19][20][21] When separating the results for unilateral versus bilateral clefts, our 90% success rate for unilateral clefts is comparable to other reported success rates of 73-94%. 5,9,[17][18][19][20][21] One study by Jabbari et al reported a higher success rate of 98% for unilateral clefts. 8 Those authors used a modified Bergland index to evaluate success, in which Bergland index score II was defined as bone loss of <¾ of the root length, and score III as bone loss of >¾ of the root length.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…5,8,[17][18][19][20][21] When separating the results for unilateral versus bilateral clefts, our 90% success rate for unilateral clefts is comparable to other reported success rates of 73-94%. 5,9,[17][18][19][20][21] One study by Jabbari et al reported a higher success rate of 98% for unilateral clefts. 8 Those authors used a modified Bergland index to evaluate success, in which Bergland index score II was defined as bone loss of <¾ of the root length, and score III as bone loss of >¾ of the root length.…”
Section: Discussionsupporting
confidence: 71%
“…Jabbari et al found that the surgical success rate declined when comparing follow-up between 10 and 20 years. 19 In our study, the mean follow-up was 7.2 years, varying from 1.7-10.8 years, and our success rates might decline with a longer follow-up time.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations